Geochemical Variations in Hydrocarbon Components Distribution in a Prograding Deltaic Sequence: A case study of the Baram Delta, Offshore Sarawak Basin, Malaysia - Ben-Awuah, Joel (2014)
Studies on hydrocarbon distribution have evolved from basic reservoir characterization to complex studies today involving the interactions between oil components and clay minerals and sequential extraction studies on hydrocarbon extracts in reservoir rocks. Findings from such studies include the discovery of variations in oil fractions in reservoirs such as adsorbed oil and free oil. The theory that first oil charge preferentially interacts with clay minerals occurring in pores and as coatings in reservoirs was also proposed by some researchers. Despite, all these studies some aspects of variations in the composition of hydrocarbons in reservoir rocks still need to be investigated further. This study has been carried out particularly because the qualitative and quantitative composition of aromatic and aliphatic components of hydrocarbons in terms of the presence and quantities of hydrocarbon functional groups and how they relate to hydrocarbon migration have not been exhaustively discussed. This study uses Ultra-Violet visible light (UV-vis) and Fourier Transform Infra Red (FTIR) to characterize variations in hydrocarbon distribution in reservoir quality sandstones from three fields namely BD01, BD02 and BD03 in the Baram Delta, offshore Sarawak and to deduce how these variations relate to differential migration patterns in hydrocarbons. Hydrocarbon extraction was done in the ultra vilolet visible (UV-vis) experiment using 0.1M sodium pyrophosphate as solvent whereas in the Fourier Transform Infra Red (FTIR), the experiment was done on very fine powdered samples of the sandstones. Results from both the UV-vis and FTIR experiments indicate a dominance of aromatic functional groups in the samples. Most of the samples have E4/E6 ratio of more than 1 which indicates a high degree of aromacity. The BD01 field sandstones with a maximum porosity of 32% has the highest average E4/E6 ratio of 1.21, followed by the BD02 field sandstones with a maximum porosity of 29% and average E4/E6 ratio of 1.19 and the BD03 field with a maximum porosity of 20% and an average E4/E6 ratio of 1.09. The dominance of aromatics in the samples is interpreted as a possible indication of episodes of migration of aliphatics in the past leaving the aromatics behind with the variations in E4/E6 ratio reflecting the micro heterogeneities in the samples. Keywords: Aliphatic, aromatic, fulvic acid, functional group, heterogeneity, humic acid, hydrocarbon components, migration, porosity